Personalized requirements oriented trustworthy services recommendation based on social network - Pei-yun ZHANG; En-hong CHEN; Bo HUANG (Tongxin xuebao)
In current background of service computing and society computing,it is difficult to obtain the trustworthy Web services to meet users' personalized requirements.To olve the problem,the trustworthy services recommendation model was proposed which orients personalized requirements based on socia twork.The decomposing and matching algorithm was proposed for users' personalized requirements,and the algorithm utilizes the semantic dictionary to improve the se-mantic match of users' requirements.Based on personal zed functional requirements and social trust values of network nodes and the services' direct trust values and indirect trust values,a trustworthy service recommendation algorithm was designed which meets the personalized requirements.By analyzing the correlation among the social network and services' trust values,the method can improve the performance of trustworthy services collaborative recommendation.The analysis of algorithms and experiments' results show that the approach is effective and feasible.